Patients' experience of patient safety information and participation in care during a hospital stay - Bojan Tubic; Caterina Finizia; Asra Zainal Kamil; Pernilla Larsson; My Engström (Wiley, 2023)
Abstract Aim Having a culture of safety is crucial when providing high‐quality health care, yet preventable adverse events are common in the Swedish healthcare system, especially in the field of surgical care. Research shows that patient participation can improve patient safety. This study aimed to explore patients' experience of the safety leaflet, "Your safety in hospital," including participation in care and feelings of safe care. Design This study uses a descriptive qualitative study design. Methods Twenty patients from surgical wards received patient safety leaflets and participated in semi‐structured interviews during their hospital stay. Data were analysed using qualitative content analysis. Results Three categories emerged from the analysis: Positive and negative experiences of provided information, Experiences of participation in own care, and Feelings of being safe arising from a perception of good quality care. Most participants were satisfied with their participation in their care and felt safe during their hospital stay. Oral information about the safety leaflet from healthcare personnel was lacking.